Degradação de resíduo de levedura empregado em biossorção por processos eletro-oxidativos avançados - Bargas, Maria Francisca Ribeiro de Aguiar [UNIFESP] (2017)
The use of agroindustrial waste as adsorbents has been evaluated as an alternative treatment of textile effluents, mainly for color removal. However, solutions are required for the proper fate of the adsorbent after sorption of the organic compound. In this way, the Advanced Oxidative Processes (POA) appear as an alternative of clean destination of the solid residues containing organic compound. The objective of this work was to evaluate the efficiency in the treatment of the degradation of dry yeast biomass, biosorbent from the residue of the sugar and alcohol industry, after the sorption of methylene blue reactive dye by means of photo-Fenton and heterogeneous photocatalysis (photocatalysis and photoelectrocatalysis) using a TiO2 nanotubular oxide layer as catalyst. The study was carried out with three yeast biomasses, washed yeast biomass (WYB), in nature Yeast Biomass (YB) and yeast biomass after the sorption of the methylene blue reactive dye (SYB). Initially the BL was washed with distilled water to remove the soluble residue in order to quantify the reduction of mass and mineralization only of the solid fraction. The optimization studies of the best conditions of degradation and mineralization of the organic matter were obtained with the WYB. The optimization studies of the best conditions of degradation and mineralization of the organic matter were obtained with the WYB. In the photo-Fenton process, the optimized condition was 2,500 mg L-1 of H2O2 and 40 mg L-1 of Fe2+ and 100 mg of biomass mass, with sequential addition of H2O2 during the degradation process, at 15 min intervals, during 2 hours of treatment, with a percentage of mineralization around 45% and destruction of the degraded biomass (lysed). While in heterogeneous photocatalysis, although there is no evidence of cell lysis, the photocatalytic treatment showed to be more efficient in reducing the organic load of the WYB and YB compared to the treatment by photoelectrocatalysis, with a mass reduction percentage of around 46,5% after 4 hours of treatment. In both studies, an irradiation source with a mercury vapor lamp of 80 W was used. Then, the combination of the optimized processes, photo-Fenton followed by photocatalysis, was employed in the treatment of YB and SYB. After the degradation, YB presented a reduction of mass and mineralization around 85% and SYB around 60% of mass reduction and 50% of mineralization. The combination of the photo-Fenton process followed by the heterogeneous photocatalysis showed to be a clean destination of solid residues formed by yeast biomass with adsorbed dye.